2013
DOI: 10.1016/j.jss.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-A inhibits EphB4 and stimulates delta-like ligand 4 expression in adult endothelial cells

Abstract: Background During vein graft adaptation to the arterial circulation, vascular endothelial growth factor (VEGF)-A expression transiently increases before becoming down-regulated; however the role of VEGF-A in venous remodeling is not clear. In addition, although VEGF-A stimulates angiogenesis and determines arterial identity in nascent arterial endothelial cells (EC), the role of VEGF-A in regulating identity in adult venous EC is also not clear. Materials and Methods EC, wild type (EphB4+/+) or heterozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…Thus, the early phase increase in VEGF-A inhibits the expression of Eph-B4 and upregulates the expression of Dll4 (a Notch ligand), but without stimulating its downstream signaling events such as Notch activation or ephrin-B2 expression in these adult ECs. These results are consistent with the effects of blocking the VEGF/COUP-TFII-Notch signaling-Eph-B4/ephrin-B2 pathway in adult ECs [55]. Therefore, vein grafts lose their venous identity markers without acquiring arterial identity.…”
Section: Vein Graftssupporting
confidence: 86%
“…Thus, the early phase increase in VEGF-A inhibits the expression of Eph-B4 and upregulates the expression of Dll4 (a Notch ligand), but without stimulating its downstream signaling events such as Notch activation or ephrin-B2 expression in these adult ECs. These results are consistent with the effects of blocking the VEGF/COUP-TFII-Notch signaling-Eph-B4/ephrin-B2 pathway in adult ECs [55]. Therefore, vein grafts lose their venous identity markers without acquiring arterial identity.…”
Section: Vein Graftssupporting
confidence: 86%
“…We previously showed that MLEC express both Eph-B4 and Ephrin-B2, consistent with a venous phenotype. 16 As expected, stimulation of endothelial cells with Ephrin-B2/Fc stimulated Eph-B4 phosphorylation, in a bimodal temporal distribution, with an early peak at approximately 1 minute and a later peak at approximately 30-60 minutes ( Figure 1A). In addition to Ephrin-B2/Fc stimulating Eph-B4 phosphorylation, Ephrin-B2/Fc also stimulated eNOS phosphorylation, in a similar bimodal pattern ( Figure 1B), that was inhibited in cells pretreated with the Eph-B4 inhibitor NVP-BHG712 ( Figure 1C).…”
Section: Resultssupporting
confidence: 78%
“…44 Another study showed that VEGF upregulates Delta-like 4 (DLL4) and presenilin expression, and increases activation of Notch4, leading to upregulation of ephrinB2 and downregulation of EphB4 in venous ECs. 45 In contrast, Yang et al 46 found that VEGF-A inhibits expression of EphB4 and stimulates expression of DLL4, but does not stimulate either Notch or ephrinB2 expression in adult venous ECs. Pretreatment with a VEGFR-2 neutralizing antibody abolishes VEGF-stimulated downregulation of EphB4, but not the upregulation of DLL4.…”
Section: Figmentioning
confidence: 92%